The new aestheticism - Joughin, John J.; Malpas, Simon (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
Introduces the idea of a new aestheticism - "new" in that it identifies a turn taken by contemporary thinkers towards the idea that focusing on the specifically aesthetic impact of a work of art or literature has the potential to open different ways of thinking about identity, politics and culture